Sistem Pakar Menentukan Tingkat Depresi Pekerja Yang di PHK Menggunakan Metode Certainly Factor - Agustinus Gunawan Siregar (JURIKOM (Jurnal Riset Komputer), 2019)
Certainty factor shows a measure of certainty about a fact or rule. As well as providing a good solution for many people. Depression in laid-off workers is a very serious problem experienced by everyone who experiences termination of employment from their place of employment, this will have an impact on increasingly uncontrolled behavior changes. The results of the level of worker depression were obtained from the certainty factor algorithm by identifying the symptoms they experienced. And certainty factor works well in analyzing the symptoms caused by the depression.